2006
DOI: 10.1007/s00442-006-0568-z
|View full text |Cite
|
Sign up to set email alerts
|

Can parasites be indicators of free-living diversity? Relationships between species richness and the abundance of larval trematodes and of local benthos and fishes

Abstract: Measuring biodiversity is difficult. This has led to efforts to seek taxa whose species richness correlates with the species richness of other taxa. Such indicator taxa could then reduce the time and cost of assessing the biodiversity of the more extensive community. The search for species richness correlations has yielded mixed results, however. This may be primarily because of the lack of functional relationships between the taxa studied. Trematode parasites are highly promising bioindicators. Diverse assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
2
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 30 publications
0
96
2
5
Order By: Relevance
“…Infected populations occur where the California horn snail, Cerithidea californica, is also present in the estuary. The trematode E. californiensis, one of the most abundant trematode parasites in these habitats (Martin 1955;Hechinger et al 2007), uses three hosts in its life cycle: horn snails (C. californica); killifish; and several species of piscivorous birds (Martin 1950). Larval E. californiensis cercariae swim out of their first intermediate snail host, penetrate the skin of F. parvipinnis and migrate to the brain, presumably following blood vessels or nerve tracts (McNeff 1978;Hendrickson 1979;Haas et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Infected populations occur where the California horn snail, Cerithidea californica, is also present in the estuary. The trematode E. californiensis, one of the most abundant trematode parasites in these habitats (Martin 1955;Hechinger et al 2007), uses three hosts in its life cycle: horn snails (C. californica); killifish; and several species of piscivorous birds (Martin 1950). Larval E. californiensis cercariae swim out of their first intermediate snail host, penetrate the skin of F. parvipinnis and migrate to the brain, presumably following blood vessels or nerve tracts (McNeff 1978;Hendrickson 1979;Haas et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Because the diversity and abundance of these additional hosts correlates with species richness and prevalence of trematodes infecting horn snails at small spatial scales (Smith 2001, Hechinger and Lafferty 2005, Hechinger et al 2007), these final and second intermediate hosts might drive some of the observed diversity patterns. However, both bird and second intermediate host richness are likely greater in the tropics, considering general diversity patterns in the ocean (Hillebrand 2004, Roy andWitman 2009).…”
Section: Possible Explanations For the Reversed Ldgsmentioning
confidence: 99%
“…2; Appendix A). We treated sites as independent samples for our analyses, because these snails have very low mobility, and trematode diversity varies over small spatial scales (Hechinger and Lafferty 2005, Torchin et al 2005, Hechinger et al 2007). We targeted the largest snails from each site for dissections, as these are generally older and have a higher probability of being infected with parasites (e.g., Kuris 1990, Sousa 1993, Torchin et al 2005.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in an unpublished thesis, Hunter (1942), also working in southern California, included what appear to be two renicolid xiphidiocercariae. More recently, ecological and evolutionary research involving this trematode guild has included what was considered to be a single, undescribed renicolid xiphidiocercaria (for example, "REN2" in Sousa (1993), and "Large Xiphidiocercaria" in Hechinger et al (2007)). A few years ago, while carefully examining the morphology of this "Large Xiphidiocercaria," it became clear that it represented not one, but two species.…”
Section: Introductionmentioning
confidence: 99%